Potent reduction of plasma lipoprotein (a) with an antisense oligonucleotide in human subjects does not affect ex vivo fibrinolysis - Boffa, Michael B.; Marar, Tanya T.; Yeang, Calvin; Viney, Nicholas J.; Xia, Shuting; Witztum, Joseph L.; Koschinsky, Marlys L.; Tsimikas, Sotirios (Journal of lipid research, 2019)
It is postulated that lipoprotein (a) [Lp(a)] inhibits fibrinolysis, but this hypothesis has not been tested in humans due to the lack of specific Lp(a) lowering agents. Patients with elevated Lp(a) were randomized to antisense oligonucleotide [IONIS-APO(a)Rx] directed to apo(a) (n = 7) or placebo (n = 10). Ex vivo plasma lysis times and antigen concentrations of plasminogen, factor XI, plasminogen activator inhibitor 1, thrombin activatable fibrinolysis inhibitor, and fibrinogen at baseline, day 85/92/99 (peak drug effect), and day 190 (3 months off drug) were measured. The mean ± SD baseline Lp(a) levels were 477.3 ± 55.9 nmol/l in IONIS-APO(a)Rx and 362.1 ± 89.9 nmol/l in placebo. The mean± SD percentage change in Lp(a) for IONIS-APO(a)Rx was −69.3 ± 12.2% versus −5.4 ± 6.9% placebo (P < 0.0010) at day 85/92/99 and −15.6 ± 8.9% versus 3.2 ± 12.2% (P = 0.003) at day 190. Clot lysis times and coagulation/fibrinolysis-related biomarkers showed no significant differences between IONIS-APO(a)Rx and placebo at all time points. Clot lysis times were not affected by exogenously added Lp(a) at concentrations up to 200 nmol/l to plasma with very low (12.5 nmol/l) Lp(a) levels, whereas recombinant apo(a) had a potent antifibrinolytic effect. In conclusion, potent reductions of Lp(a) in patients with highly elevated Lp(a) levels do not affect ex vivo measures of fibrinolysis; the relevance of any putative antifibrinolytic effects of Lp(a) in vivo needs further study.